BS ISO 11999-4. PPE for firefighters. Test methods and requirements for PPE used by firefighters who are at risk of exposure to high levels of heat and/or flame while fighting fires occurring in structures. Part 4. Gloves (14th August 2023) - British Standards Institution,
No abstract available